The Role of Marketing Culture in Enhancing Marketing Performance: A Field Research in Abu- Ghraib Dairy Factory - Abdul- Razzaq, Nour Qusay; Jasim, Abdullah Basem; Bakr, Farooq Omar (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to study the role of marketing culture in enhancing marketing performance by examining the relationship and impact models between them, as the study problem was embodied by questions, including: What is the role of marketing culture in enhancing marketing performance and what is the truth about the relationship between them in the researched organization ?, So the study sample was represented by an Intentional sample, consisting of (32) employees, which included all the personnel working in the marketing department, customer service, and managers at the upper and middle administrative levels. The questionnaire was adopted as a main measurement tool for the study in addition to personal interviews to collect data. The study also relied on the descriptive and analytical approach to present and analyze the data. Several statistical methods have been employed to analyze these data, the most prominent of which are (Pearson Correlation Coefficient, Simple Regression Analysis Method, F- Test and t). Among the most important conclusions reached by the study: The overall marketing culture of the researched organization has influenced the activities and indicators that enhance its marketing performance. As for the most important recommendations presented by the study: The need for the researched organization to benefit from the support of the administration and workers to enhance the marketing culture in the organization by setting the reference framework for the work within the organization and the principles and foundations that guide and govern the work of all individuals working in the organization and focus on the dimensions of the marketing culture to support and enhance the marketing performance.